Soldiers and Scholars Military Education and National Policy - Masland, John Wesley (Princeton Legacy Library, 2015)
The traditional distinction between military and political affairs in American life has become less significant as military officers increasingly participate with civilians in the formulation of national policies. In an examination of the impact of this change upon professional military education, the authors present a forthright analysis of military responsibility today, the growth of education for policy roles, the form and content of that education, and its relation to the over-all duties of the armed forces. They have used hundreds of interviews and questionnaires and studied carefully the history and programs of the military academies, ROTC, Command and Staff Schools, Armed Forces Staff College, National War College, three service War Colleges, Industrial College of the Armed Forces, and other institutions.Originally published in 1957.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905